A preliminary annotated bibliography of materials on Indonesia written and/or published in the Philippines, 1936-1982 - Laoccong, Mustafa; Buenrostro, Juan Jr. C.; Vallejo, Rosa M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1983)
There are many materials about Indonesia written or published in the Philippines. These can be found in many libraries in the form of books, pamphlets, periodical and newspaper articles as well as theses and dissertations.
This study attempts to compile an annotated bibliography of materials on Indonesia written and/or published in the Philippines, 1936-1982 based on locally found resources such as bibliographies, book and card catalogs, and printed and local indexes. The researcher visited fourteen libraries, state and private as well as those belonging to universities and colleges located in Metro Manila, Los Baños and Silang, Cavite. This bibliography contains 542 items, arranged according to type of materials as follows: pamphlets, 15 items; periodical articles, 126 items; newspaper articles, 273 items; theses and dissertations, 93 items; and report and conference papers, 33 items. It was found that the oldest material appeared in 1936, hence this bibliography covers the period from 1936 up to 1982. An author index and a subject index are found at the end of the bibliography.
The main problem in the collection of data is that many libraries were very selective in their policy of storage of such kind of materials, especially in the making tools of access like card and book catalogs, indexes of author and titles as well as subject arrangements. Many articles might have been missed by this researcher because of this problem.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Indonesia--Bibliography.